Production Of Bio-Oil Via Catalytic And Non-Catalytic Hydrothermal Liquefaction Of Spirulina - Teng, Siong Lim (Universiti Sains Malaysia, 2018)
Hydrothermal liquefaction process has been proven as a promising method to produce bio-oil from microalgae. For the rationale to improve the yield and quality of the bio-oil, the effect of catalytic and non-catalytic hydrothermal liquefaction of spirulina as a feedstock was investigated. The process was performed at a fixed spirulina to water content (10 g/100 ml) at 270 °C in a batch reactor. Various operating parameters (effect of reaction time, effect of catalyst type and effect of catalyst dosage) were investigated for the rationale to attain the highest yield accompanied by the presence of high quality of bio-oil. The effect of reaction time was varied from 0 to 40 min and the highest yield of bio-oil was obtained at 20 min (39 %). Various type of catalysts such as zeolite-HY, K₂CO₃ , Al₂O and MgO were tested on the production of bio-oil and the highest yield of bio-oil was obtained by zeolite HY (41 %) followed by K₂CO₃, Al₂O₃ and MgO with 38.6, 38.1, and 23.8 %, respectively. In fact, the presence of zeolite HY managed to improve the percentage of C and H content while decreasing the N and O values as compared to the feedstock. The effect of catalyst dosage (0.01 to 0.5 g) was then performed and only 0.1 g of catalyst was required to attain the highest yield of bio-oil (49.2 %). The C and H content of the bio-oil obtained from catalytic HTL were found to be higher than those of the blank experiment while the O, N, and S contents of the bio-oil from the catalytic HTL were also lower than those of the blank experiment. Zeolite-HY catalyst managed to produce bio-oil of higher quality as it contain the highest C and H content and lowest in O content among the tested catalysts. The HHV of bio-oil produced from a blank sample (29 MJ/kg) was relatively lower compared to the value of bio-oil produced in the presence of 0.1 g zeolite catalyst (35 MJ/kg). The main components present in bio-oil produced from catalytic and non-catalytic HTL were categorized into carbonyls, acids, hydrocarbons, aromatics, alcohol, and ketone. Overall, zeolite HY managed to be recycled for 4th time of repetitions and only slight reductions in the yield of bio-oil was observed.